ANALYSIS OF THE DETERMINANTS OF CONSUMER DECISIONS IN PURCHASING HALAL BEAUTY PRODUCTS - Eritrina Rizki Chairani; Qurtubi; Imam Djati Widodo; Rahma Fariza (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2021)
Halal beauty products have now begun to attract the attention of the Muslim community in Indonesia, but it does not necessarily show that consumers of halal beauty products prioritize halal products, because there are other factors that can affect purchasing decisions. The purpose of this study is to determine the influence of product quality, halal label, and product price on the purchase decision of halal beauty products, which then based on these results, an evaluation of the level of awareness and concern of female students for halal is carried out. The data was collected by distributing questionnaires to students of University X. The respondents who filled out this research questionnaire were active students of University X who had bought halal beauty products of any brand. This research method is SEM-PLS analysis to predict the influence between independent variables on dependent variables, as well as descriptive analysis to determine the level of awareness and concern of female students for halal. The result of this study is that the three variables each have a positive and significant effect on purchasing decisions. Based on the results of the SEM-PLS pathway coefficient test, it is known that product quality has a greater influence than the halal factor (halal label) when female students decide to buy halal beauty products. Therefore, a further evaluation of the level of halal awareness and concern is carried out by conducting a descriptive analysis on each item of halal label indicators. Through this analysis, the results were obtained that 62.5% of the eight halal label indicator items were in the range of positive categories which showed that the level of halal awareness and concern of female students was high.